Self-management-competency as a new target in Hidradenitis suppurativa care - C. Mann; P. Staubach; S. Grabbe; J. Wegner; K. Hennig; G. Nikolakis; J. C. Szepietowski; L. Matusiak; E. von Stebut; U. Kirschner; M. Podda; S. Garcovich; et al. (Taylor & Francis Group, 2023)
Background: Hidradenitis suppurativa affects approximately 1% of the population. Objective: Highlighting the relevance of self-management-competency as a new therapeutic target. Method: 258 patients from the 'Epidemiology and Care in Acne inversa (EpiCAi)' project were included in the study. Disease burden was measured by patient-rated questionnaires in terms of disease activity, pain, quality of life, depression and insomnia and correlated with the domains of the health education impact questionnaire (heiQ) measuring self-management-competency. Results: 66 male (25.6%) and 192 female (74.4%) patients, with a mean age of 40.3 ± 10.24 years were included. Mean scores of pain on the numeric rating scale (NRS), Dermatology Life Quality Index (DLQI) and Hospital Anxiety and Depression Scale (HADS) were 5.11 ± 2.68, 11.35 ± 7.79 and 13.71 ± 7.57, respectively. The Insomnia severity index (ISI) showed a mean of 9.58 ± 5.76. The HADS has the highest increased total risk across all heiQ domains. With respect to the heiQ domains, the highest exposure can be attributed to improving constructive attitudes and approaches as well as decreasing emotional distress. Conclusion: There is a clear association of self-management-competency with overall disease burden, which underlines the need for psychoeducational support. This study provides ideas to develop new possible strategies of care.